2000
DOI: 10.1002/(sici)1097-0215(20000415)86:2<174::aid-ijc5>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Vegf, vegf-B, vegf-C and their receptors KDR, FLT-1 and FLT-4 during the neoplastic progression of human colonic mucosa

Abstract: Because the crucial role of angiogenesis has been demonstrated in tumor growth and metastasis, the present study was undertaken to characterize the relative expression of vascular endothelial growth factors VEGF (vascular endothelial growth factor), VEGF‐B, VEGF‐C, and their receptors KDR (kinase insert domain‐containing receptor), FLT‐1 (fms‐like tyrosine kinase), and FLT‐4 in human colonic cancers, in relation to the Astler‐Coller pathological classification, and to prognosis. VEGF and VEGF‐B gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(68 citation statements)
references
References 15 publications
7
60
0
1
Order By: Relevance
“…Hypoxic environment has been shown to play a major role in tumor angiogenesis, cancer growth, and metastasis. The hypoxia-dependent angiogenic switch in human solid tumors is an early event linked to the secretion of high levels of VEGF and several angiogenic factors by cancer cells, as well as by endothelial cells or other cell types in the tumor stroma (Andre et al, 2000). The NO/cGMP/ PKG and calcium-dependent signaling pathways are also involved in the regulation of tumor cell invasiveness and angiogenesis linked to endothelial cell proliferation, morphogenesis, and tumor invasion (Kawasaki et al, 2003).…”
Section: Promotion Of Par-1 Proinvasive Activity By Hypoxiamentioning
confidence: 99%
“…Hypoxic environment has been shown to play a major role in tumor angiogenesis, cancer growth, and metastasis. The hypoxia-dependent angiogenic switch in human solid tumors is an early event linked to the secretion of high levels of VEGF and several angiogenic factors by cancer cells, as well as by endothelial cells or other cell types in the tumor stroma (Andre et al, 2000). The NO/cGMP/ PKG and calcium-dependent signaling pathways are also involved in the regulation of tumor cell invasiveness and angiogenesis linked to endothelial cell proliferation, morphogenesis, and tumor invasion (Kawasaki et al, 2003).…”
Section: Promotion Of Par-1 Proinvasive Activity By Hypoxiamentioning
confidence: 99%
“…Quantitative analysis of VEGF-A in CRC tissue and normal colonic and rectal tissue has been performed in several studies, and high levels of tumour VEGF-A have been correlated with poor prognosis (Andre et al 2000;George et al 2001;Broll et al 2001;Ferroni et al 2005;Kuramochi et al 2006;Altomare et al 2007). In general, VEGF-A seems to be up-regulated in CRC compared to normal tissue at both mRNA and protein level, but the possible relationship with SNPs needs further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies showed that VEGF expression at the tissue level is not a good predictor of prognosis. 8,12,13 Placenta growth factor (PlGF), a dimeric glycoprotein with 53% homology to VEGF, 14,15 which binds to VEGF receptor-1 (Flt-1), but not to VEGF receptor-2 (Flk-1), may function by modulating VEGF activity. 16 Flt-1 exists in two forms due to alternative splicing: the full-length receptor, which transmits angiogenic signals, and a soluble secreted form of Flt-1 (sFlt-1), which lacks the transmenbrane and cytoplasmic domains but retains the ability to bind to its ligands.…”
mentioning
confidence: 99%